2005
DOI: 10.1063/1.2008253
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of lattice hard-sphere models

Abstract: Thermodynamic properties of several lattice hard-sphere models were obtained from grand canonical histogram- reweighting Monte Carlo simulations. Sphere centers occupy positions on a simple cubic lattice of unit spacing and exclude neighboring sites up to a distance sigma. The nearestneighbor exclusion model, sigma = radical2, was previously found to have a second-order transition. Models with integer values of sigma = 1 or 2 do not have any transitions. Models with sigma = radical3 and sigma = 3 have weak fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 31 publications
5
50
3
Order By: Relevance
“…Note that the maximum density is 1/2. In higher dimensions [24,30,31,54,55,56,57,58] and other geometries (see [40] and references therein), the same kind of transition is observed, also belonging to the Ising universality class.…”
Section: A Nearest Neighbor Exclusion (1nn)mentioning
confidence: 67%
See 2 more Smart Citations
“…Note that the maximum density is 1/2. In higher dimensions [24,30,31,54,55,56,57,58] and other geometries (see [40] and references therein), the same kind of transition is observed, also belonging to the Ising universality class.…”
Section: A Nearest Neighbor Exclusion (1nn)mentioning
confidence: 67%
“…Interestingly, no transition was found for the analogous d = 3 system of hard-cubes with λ = 2 [58] on a cubic lattice. On the other hand, nearest and next nearest neighbors exclusion in d = 3 presents a weak first order transition [58]. Other lattices have also been considered, see Refs.…”
Section: B Nearest and Next-nearest Neighbors Exclusion (2nn)mentioning
confidence: 98%
See 1 more Smart Citation
“…44 Our model also derives inspiration from the "finely discretized" lattice model of Panagiotopoulos. 45,46 To elaborate, colloids C are discretized hard disks (HD) with a radius R, measured in number of lattice sites, and occupy a set of sites S C = {r i | d(r i ,r C ) ≤ R}, where r C are the lattice coordinates of the disk, r i are the coordinates of lattice site i, and the function d(a, b) calculates the absolute distance between a and b using the minimum image convention. The disks have only translational degrees of freedom, and their Hamiltonian H C (in the absence of the solvent mixture) is zero for non-overlapping configurations, and is infinite if any pair of colloids overlap, or if a colloid and solvent site overlap.…”
Section: Modelmentioning
confidence: 99%
“…The use of lattice models has proven to be very fruitful [18][19][20][21][22][23][24][25][26][27][28] in the analysis of the phase diagram of simple models with complex phase behaviour, with the advantage that simulations can be performed for larger system sizes with higher accuracy. For example, it has been shown that it is possible to design associating lattice models that reproduce some of the behaviour of water, including the density and diffusion anomalies [22,27,28].…”
Section: Introductionmentioning
confidence: 99%